Teachers Skills in Using Audio-Visual Media for Fardhu Prayer Instruction in Grade II of Elementary School - Achmadi, Achmadi; Jennah, Rodhatul; Muzakki, Muzakki (Jayapangus Press, 2025)
The teacher's skill in using audio visual media is the teacher's ability to operate and utilize media that combines audio (sound) and visual (image) elements effectively in the learning process. This study aims to determine how the teacher's skills in using audio-visual media, especially on the material of fardhu prayer in class II of Tahfidz Al-Jamiel Elementary School. The method used in this research is a qualitative method with a descriptive type that aims to explain the data naturally, objectively and realistically with the aim of searching and finding information. Islamic Religious Education Teacher of Tahfidz Al-Jamiel Elementary School Palangka Raya as the research subject. The informants in this study were the principal and students. The results showed that from planning, implementation to follow-up, it was carried out effectively. In planning, teachers choose media that is in accordance with the material and characteristics of grade II elementary school students. During implementation, teachers operate the media well, keeping students focused and engaged. After learning, teachers provide opportunities for students to repeat the material, and conduct evaluations in the form of assessments to measure the extent of students' understanding during the learning process. As for obstacles, there are several obstacles faced by teachers, such as limited time to prepare appropriate media and technical problems with the tools used. Nonetheless, teachers still try to ensure students understand the material taught and work to overcome these obstacles. Teachers also continue to innovate and develop their skills in the use of audio-visual media so that the learning process remains interesting and not monotonous for students to support the smooth learning process.